Diversified Photo/Electronic Functions Based on a Simple Chalcone Skeleton: Effects of Substitution Pattern and Molecular Packing. (18th January 2018) - Cheng, Xiao; Wang, Zhaoyang; Tang, Baolei; Zhang, Hongyu; Qin, Anjun; Sun, Jing Zhi; Tang, Ben Zhong
Abstract: Structurally simple chalcone derivatives1–2 are prepared and their diversified emission behaviors are deeply investigated. Two polymorphs (1G : λem = 536 nm, Φ f = 0.08, τ = 1.81 ns;1O : λem = 573 nm, Φ f = 0.19, τ = 10.82 ns) with distinctively different emission behaviors are constructed by finely controlling the crystallization conditions of compound1 .1G exhibits typical amplified spontaneous emission while1O shows an interesting blue shift under smashing process (1O‐S : λem = 562 nm, Φ f = 0.23, τ = 6.42 ns), which is ascribed to their different molecular packing structures and intermolecular interactions. Notably, simply introducing a fluorine substituent effectively endows the crystal with red emission (crystal2 : λem = 598 nm, Φ f = 0.16, τ = 18.77 ns). Thus multicolor emissions including green, yellow, orange, and red emissions are obtained based on this simple chalcone skeleton. Abstract : Polymorphs 1G (λem = 536 nm, Ф f = 0.08, t = 1.81 ns) and 1O (λem = 573 nm, Ф f = 0.19, τ = 10.82 ns) displaying distinctively different emission behaviors are obtained based on a structurally simple D‐A (Donor‐Acceptor) type molecule. Notably, simply introducing a fluorine substituent effectively endows the crystal with red emission (crystal 2: λem = 598 nm, Ф f = 0.16, t = 18.77 ns).